Kausalitas Pembangunan Keuangan dan Pembangunan Sumber Daya Manusia di ASEAN-4 - Yohana Wahyu Prasetyowatie; Cynthia Yohanna Kartikasari; Muhammad Wisnu Girindratama (Owner : Riset dan Jurnal Akuntansi, 2022)
The study analyzed the effect of Financial Development on Human Development from 2009 to 2020 in ASEAN-4 countries. Financial development is projected with domestic credit for the private sector, broad money ratio, economic growth, openness, inflation, and the proportion of government expenditure to GDP, while human development is projected with HDI. The tests used a data panel, and the results showed that domestic credit for the private sector had a significant effect on the increase in HDI values.